THE PROBLEM OF PEDAGOGICAL ACCENTOLOGY IN EDUCATION OF MORAL PERSONALITY ON CURRENT STAGE OF DEVELOPMENT UKRAINIAN SOCIETY (Pedagogy of Higher and Secondary Education, 2007)
In clause the tasks, principles of education of the moral person in a context of development of the Ukrainian society in the beginning XXI of century are considered the purpose.